2008
DOI: 10.1002/adem.200700196
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Characterization of Alloy 625 Deposited on Nickel Foam using Air Plasma Spraying

Abstract: Sandwich constructions offer many advantages over traditional stiffened shapes including light weight, high strength to weight ratio, and high stability. The basic concept of sandwich structures consists of two thin skins (faces) and a lightweight thicker core. The skin materials may be metallic, wood, or composite laminates, while cores can be made from a variety of materials including metallic and nonmetallic honeycombs, cellular metallic or polymeric foams. [1,2] Foam structures are attractive due to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The term Inconel refers to a family of alloys with slightly different compositions and contains Ni as the main element, up to 25% of Cr, Fe, Mo, and Nb, and other metals in varied amounts . The other elements are added to accomplish specific characteristics, such as corrosion resistance, grain structure, high temperature stability, strength hardness, elasticity, and ductility. , Previous research on these acid resistant materials focused on bulk materials that were true alloys. Since Inconel and FE2 foams are not true alloys, their behavior in strongly acidic solutions cannot be easily related to the behavior of analogous bulk materials.…”
Section: Resultsmentioning
confidence: 99%
“…The term Inconel refers to a family of alloys with slightly different compositions and contains Ni as the main element, up to 25% of Cr, Fe, Mo, and Nb, and other metals in varied amounts . The other elements are added to accomplish specific characteristics, such as corrosion resistance, grain structure, high temperature stability, strength hardness, elasticity, and ductility. , Previous research on these acid resistant materials focused on bulk materials that were true alloys. Since Inconel and FE2 foams are not true alloys, their behavior in strongly acidic solutions cannot be easily related to the behavior of analogous bulk materials.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, one EDS scan spectrum and results (relative error of EDS can be as high as 2%) of the as-received feedstock powder are given in Table 1, respectively, showing agreement within the relative error with the manufacturer-provided values (Table 1). Powder XRD (Figure 2c) showed that the main peaks are related to the prevalent fcc γ-Ni phase [16]. Since Mo and Nb were present in the matrix as solid solution hardening alloying elements, no characteristic peaks were detected for these elements.…”
Section: Powder Feedstockmentioning
confidence: 97%
“…The mechanical performance of this type of sandwich structure depends on the properties of the coating since it carries almost all of the loads while the substrate acts as a low density supporting component. Previous results showed that the microstructural characteristics of the coating affect its mechanical properties [4,5]. For example, porosity in the coatings could exponentially decrease the yield and ultimate tensile strength of the structure.…”
Section: Introductionmentioning
confidence: 98%
“…The microstructural characteristics of the as-sprayed Inconel 625 were investigated by the authors and results were given in details elsewhere [4]. Since the microstructural features of the as-sprayed alloy Inconel 625 differ from those of the conventionally manufactured material, its response to the conventional heat treatment schedules may result in completely different mechanical properties compared to those expected for conventionally manufactured alloys.…”
Section: Introductionmentioning
confidence: 99%